Effects of controlled atmosphere on quality of minimally processed apple (cv. jonagored) - Rocha, Ada Margarida Correia Nunes (2011)
Controlled atmosphere (2% O2+ 4% to 12% CO2) storage was found to be advantageous over air storage in terms of overall preservation of fresh-cut apple (cv. Jonagored). After 3 days, CA-stored apple cubes were firmer, showed better color and higher content of fructose and soluble solids content than air-stored cubes. In relation to color preservation this benefit was increased when CO2 in the atmosphere was increased to 12% CO2. Controlled atmosphere storage showed no advantage over air storage in relation to sensory evaluation of firmness and flavor.